Multi-echelon inventory management in supply chains with uncertain demand and lead times:: literature review from an operational research perspective - Gumues, A. Taskin; Guneri, A. Fuat (SAGE PUBLICATIONS LTD, 2007)
Historically, the echelons of the supply chain, warehouse, distributors, retailers, etc., have been managed independently, buffered by large inventories. Increasing competitive pressures and market globalization are forcing firms to develop supply chains that can quickly respond to customer needs. To remain competitive and decrease inventory, these firms must use multi-echelon inventory management interactively, while reducing operating costs and improving customer service. The current paper reviews the literature, addressing multi-echelon inventory management in supply chains from 1996 to 2005. The behaviour of the papers against demand and lead-time uncertainty is the key analysis point of the literature review presented here and it is conducted from an operational research point of view. Finally, directions for future research are suggested.
Keywords: supply chain; multi-echelon inventory management; demand uncertainty; leadtime uncertainty; OPTIMAL POLICIES; DIVERGENT SYSTEMS; ORDERING POLICIES; INFINITE-HORIZON; ONE-WAREHOUSE; OPTIMIZATION; MODEL; ALLOCATION; INFORMATION; STOCKING; Engineering